The effect of velocity-specific strength training on peak torque and anaerobic rowing power - Bell, G. J.; Petersen, S. R.; Quinney, A. H.; Wenger, H. A. (Journal of Sports Sciences, 1989)
Eighteen varsity oarsmen from the University of Victoria were divided into three training groups: (a) high-velocity repetition (HVR) training, (b) low-velocity repetition (LVR) training, and (c) a no-training control. Rowing-specific exercises were performed on Hydra-Fitness machines in a repeated circuit format with the HVR group performing 18 to 22 repetitions and the LVR group performing six to eight repetitions of each exercise. Training effects were measured on a rowing ergometer. A 90-seconds maximum performance was measured every 15 seconds with the 15 to 30 seconds interval being used as the measure of peak power output. The high lactic acid levels recorded in the subjects validated the test as being a measure of anaerobic capacity and power output. Implication: Traditional use of resistance training programs that are "meant" to improve performance should be questioned. The only time that resistance training may be of value would seem to be in the transition (off-season) for basic preparatory training phases. There is the possibility that fatigue generated by strenuous resistance activities will: (a) diminish the physical resources that can be applied to specific beneficial training; (b) detract from the amount of available training time so that the volume of specific beneficial training is reduced; and (c) the training effects from resistance training will be incompatible and interfere with beneficial specific training effects (principally those of aerobic adaptation).